VISUAL CONTRAST SENSITIVITY CARDS FOR PEDIATRIC SUBJECTS (2020)
A visual stimulus for a set of contrast cards is provided which comprises a hollow outer circle, opposing and identical first and second arc segment within the outer circle which are symmetrical about the vertical diameter of the outer circle, a first filled-in circle and a second filled-in circle being identical in diameter to the first filled-in circle, each residing on opposite ends of the horizontal diameter of the outer circle and each being equidistant from the center of the outer circle, a filled-in center element having a rotational center on the center of the outer circle, the center element being symmetrical about both the horizontal and vertical diameter of the outer circle.